Perancangan Tata Letak Penyimpanan Material di Gudang Packaging PT X - Rachel Christina; Herry Christian Palit (Jurnal Titra, 2020)
PT X is a multinational manufacturing company located in Surabaya that produce mosquito coils. The current warehouse system is using a random storage method where the same code materials are storage separatedly. Random method that company use occurs high number of materials’ moment displacement and transportation time. The main purpose of this research is to design material’s storaging layout with classbased storage method that minimizing moment displacement and transportation time. Minimizing moment displacement is done by ABC classification, family grouping, and material’s placement at storage while transportation time is measured by Promodel simulation from the storage area to warehouse exit. There are two main proposed soulution in this research the first is dedicated storage location for each material’s type for first floor warehouse and the second is devided storage area into three area based on classification and distance measurement for second floor warehouse. Results of this proposed soulutions are reducing moment displacement as 25.12% and 21.51% for first and second floor warehouse also minimizing average transportation time as 3.94 minutes.